4(5-2v)-6v=4(-7v-5)+6v

Simple and best practice solution for 4(5-2v)-6v=4(-7v-5)+6v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5-2v)-6v=4(-7v-5)+6v equation:


Simplifying
4(5 + -2v) + -6v = 4(-7v + -5) + 6v
(5 * 4 + -2v * 4) + -6v = 4(-7v + -5) + 6v
(20 + -8v) + -6v = 4(-7v + -5) + 6v

Combine like terms: -8v + -6v = -14v
20 + -14v = 4(-7v + -5) + 6v

Reorder the terms:
20 + -14v = 4(-5 + -7v) + 6v
20 + -14v = (-5 * 4 + -7v * 4) + 6v
20 + -14v = (-20 + -28v) + 6v

Combine like terms: -28v + 6v = -22v
20 + -14v = -20 + -22v

Solving
20 + -14v = -20 + -22v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '22v' to each side of the equation.
20 + -14v + 22v = -20 + -22v + 22v

Combine like terms: -14v + 22v = 8v
20 + 8v = -20 + -22v + 22v

Combine like terms: -22v + 22v = 0
20 + 8v = -20 + 0
20 + 8v = -20

Add '-20' to each side of the equation.
20 + -20 + 8v = -20 + -20

Combine like terms: 20 + -20 = 0
0 + 8v = -20 + -20
8v = -20 + -20

Combine like terms: -20 + -20 = -40
8v = -40

Divide each side by '8'.
v = -5

Simplifying
v = -5

See similar equations:

| 14/7 | | f(d)=-2d-3 | | 4x+4x-5=27 | | -12+4e+10-7e= | | 1-m=6-6 | | -2(4-11)= | | 7x+10=-5x-86 | | -12x-19=-57 | | 36.663=p+11.363 | | d=-2d-3 | | x^2-3x+8=x^2-5x+10+2x+2 | | 4y-70=12y-3 | | y+13=98 | | 4+x/6=5 | | 1-5r=11 | | -18+o=18 | | 6+6x=4x+0 | | 6-4d=16+9d | | x^2-310x+24025=0 | | -12k+14k= | | 4+4=5 | | (4/5)*12 | | 15/m=m/5 | | 3-3u=12 | | -3/4x-5/8=-5/8x-3/4 | | 5n+8=90 | | 1/2(15+7d)=-d/7 | | 5x+13=10x-7 | | 1.4m-0.6(m-2)=2 | | (4/5)/12 | | 2-3x=4x-75 | | 1800-60x+1200-45x=c |

Equations solver categories